Mental health, COVID-19 burden and quality of life of kidney transplant recipients two years after the COVID-19 pandemic - De Pasquale, Concetta; Pistorio, Maria Luisa; Veroux, Massimiliano; Barbagallo, Noemi; Cottone, Provvidenza Marisa; Ekser, Burcin; Lorenzano, Giuseppina; Giaquinta, Alessia; Veroux, Pierfrancesco (Frontiers in Psychiatry, 2024)
the psychopathological impact of the COVID-19 pandemic in kidney transplant recipients two years after the first phase of the pandemic by outlining the trajectory change over time of symptoms at 12 and 24 months of follow-up.This is a follow-up study. We performed a study published in 2021 (phase 1 of COVID-19); of the 89 kidney transplant recipients evaluated in this study, 60 completed the 12 months follow-up (March 2021 June 2021, phase 2 of COVID-19) and 57 completed the 24 months follow-up (March 2022 June 2022, post COVID-19). The same tools as in previous study were administered: the ad hoc questionnaire on emotional state and psychophysical well-being during COVID-19, the Middlesex Hospital Questionnaire (MHQ) to provide a simple and rapid quantification of the psychological and somatic symptoms main symptoms and relevant traits and the Short Form Health Survey 36 (SF-36) was used to assess health-related quality of life. the perception of physical and emotional health.Compared to the first and second phase of COVID-19, the mean score of quality of life variables were higher in the post COVID-19 phase; thus the recipients physical health, mental health and their perception of their general health improved. Regarding the psychopathology variables the levels of Anxiety, Depression and Phobia in the Post COVID-19 phase decreased, while the Somatization score was higher. Lastly, burden of COVID-19 scores in the third phase, significantly decreased.This study Our study highlights a significant association between mental health and the burden of COVID-19 confirmed the strong mental health impact of the last two years of the COVID-19 pandemic in kidney transplant recipients. This study showed, a significant worsening, over time, of some specific symptoms, such as somatization and phobias. However, the results showed that depressive symptoms improved during the study period. even if other dimensions of mental health, such as depression, gradually reduced. Longterm monitoring of kidney transplant recipients therefore remains fundamental. These results confirmed the need to provide integrated multidisciplinary services to adequately address the long-term effects of the COVID-19 pandemic on the mental health of the most vulnerable subjects.